2015
DOI: 10.1016/j.neuropharm.2015.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Chronic baclofen desensitizes GABAB-mediated G-protein activation and stimulates phosphorylation of kinases in mesocorticolimbic rat brain

Abstract: The GABAB receptor is a therapeutic target for CNS and neuropathic disorders; however, few preclinical studies have explored effects of chronic stimulation. This study evaluated acute and chronic baclofen treatments on GABAB-activated G-proteins and signaling protein phosphorylation as indicators of GABAB signaling capacity. Brain sections from rats acutely administered baclofen (5 mg/kg, i.p.) showed no significant differences from controls in GABAB-stimulated GTPγS binding in any brain region, but displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…The precise mechanism of tolerance induction is not known, as only few studies have focused on chronic systemic baclofen treatment and results in the literature are conflicting. One proposed mechanism is downregulation of the GABA B receptor-binding sites or phosphorylation of downstream signaling regulators (Keegan et al, 2015;Lehmann et al, 2003;Pacey, Tharmalingam, & Hampson, 2011). In addition, evidence has been published on cross talk between GABA B receptor and mGluR5 receptor after chronic treatment (Pacey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanism of tolerance induction is not known, as only few studies have focused on chronic systemic baclofen treatment and results in the literature are conflicting. One proposed mechanism is downregulation of the GABA B receptor-binding sites or phosphorylation of downstream signaling regulators (Keegan et al, 2015;Lehmann et al, 2003;Pacey, Tharmalingam, & Hampson, 2011). In addition, evidence has been published on cross talk between GABA B receptor and mGluR5 receptor after chronic treatment (Pacey et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic baclofen produces many changes in the brain that could impact connectivity. We have previously mentioned that chronic baclofen produces plastic changes in regions of the reward system, including desensitization in G-protein-dependent systems and alterations in signaling of several kinase cascades (FAK, GSK3ß, DARPP-32) that are resistant to desensitization ( 37 ). In addition, AUD is associated with marked brain neuro-immune alterations ( 110 ); and studies have shown that baclofen has anti-inflammatory and neuroprotective effects on the brain.…”
Section: Long-term Network Alterationsmentioning
confidence: 99%
“…Preclinical studies have highlighted such plastic effects of baclofen or other GABA-B agonists on brain systems after chronic treatment. Keegan et al have shown that rats treated chronically with baclofen have significant decreases in G-protein-dependent signal transduction (measured by GTP-gamma-S binding) in the frontal cortex, septum, amygdala, and parabrachial nucleus ( 37 ). Such decreases demonstrate a general desensitization of G-protein-dependent systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because GABA regulates neuronal excitability and GABA receptors are widely distributed throughout the brain and the nervous system, drugs targeting GABA receptors can profoundly regulate behaviour . GABA B , one of the major GABA receptors, belong to the G protein‐coupled receptor family and are generally considered to be excellent drug targets . The GABA B receptors play an important role in the treatment of depression and anxiety .…”
mentioning
confidence: 99%
“…[1] GABA B , one of the major GABA receptors, belong to the G protein-coupled receptor family and are generally considered to be excellent drug targets. [2] The GABA B receptors play an important role in the treatment of depression and anxiety. [3] However, conventional drug development targeting GABA B receptors mainly focuses on agonists and antagonists which have the limitations of side effects, poor pharmacokinetics, and the development of tolerance.…”
mentioning
confidence: 99%